Validation of the REM sleep behavior disorder screening questionnaire in the Czech population - Bušková, Jitka; Peřinová, Pavla; Miletínová, Eva; Dušek, Petr; Růžička, Evžen; Šonka, Karel; Kemlink, David (BMC neurology, 2019)
BACKGROUND: Idiopathic rapid eye movement sleep behavior disorder (iRBD) affects 1-2% of people over 60 years of age and presents a high risk of developing a neurodegenerative disorder from the group of synucleinopathies, such as Parkinson's disease, dementia with Lewy bodies and multiple system atrophy. Therefore, screening tools are needed. In 2007, the rapid eye movement sleep behavior disorder screening questionnaire (RBD-SQ) was developed and has been translated into several languages. The aim of study was to assess the validity and reliability of the Czech version of the RBD-SQ in a mixed population of sleep clinic patients, supplemented by healthy volunteers and RBD patients. METHODS: Participants included 81 iRBD patients, 205 patients with other sleep disorders (obstructive sleep apnea, insomnia, restless legs syndrome and periodic limb movement disorder, other parasomnias, or central hypersomnias including narcolepsy) and 20 healthy volunteers. RESULTS: The mean RBD-SQ score in the iRBD patients was 9.4 ± 2.8 points, and in the non-RBD group it was 4.5 ± 3.0 (P < 0.0001). Receiver -operator analysis yielded an area under the curve of 0.864, suggesting good diagnostic performance of the scale. When using a cut-off value for positivity of 5 points, sensitivity was 0.89 and specificity was 0.62. CONCLUSIONS: The Czech version of the RBD-SQ is a sensitive tool for screening for iRBD patients and helps to identify subjects for complete clinical workup.
Keywords: senioři; Self administered questionnaire; Reproducibility of Results; reprodukovatelnost výsledků; Screening for synucleinopathy; Rapid eye movement sleep behavior disorder; Česká republika; Middle Aged; průzkumy a dotazníky; Sensitivity and Specificity; mužské pohlaví; Translating; Czech Republic; Mass Screening; ženské pohlaví; Humans; překládání; Surveys and Questionnaires; lidé středního věku; senzitivita a specificita; REM Sleep Behavior Disorder; Female; Aged; plošný screening; porucha chování v REM spánku; lidé; Male